2015
DOI: 10.4103/0970-9185.155155
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of continuous infusion and intermittent bolus administration of 0.1% ropivacaine with 0.0002% fentanyl for epidural labor analgesia

Abstract: Background and Aims:Minimal consumption of local anesthetic and opioid for epidural labor analgesia has been advocated for safe obstetric outcome and superior maternal satisfaction. The primary objective of this study was to evaluate and compare the analgesic efficacy of mode of administration of epidural 0.1% ropivacaine with 0.0002% fentanyl via continuous infusion or intermittent boluses during labor.Material and Methods:Sixty term primi or second gravida healthy parturients in labor requesting epidural ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…and Patkar et al . [513] The rise in heart rate among parturients as observed in our study was attributed to administration of intravenous injection valethamate bromide for enhancing the dilatation of cervix. [17]…”
Section: Discussionmentioning
confidence: 58%
“…and Patkar et al . [513] The rise in heart rate among parturients as observed in our study was attributed to administration of intravenous injection valethamate bromide for enhancing the dilatation of cervix. [17]…”
Section: Discussionmentioning
confidence: 58%
“…Ropivacaine has a high threshold for cardiovascular toxicity, and it has been reported that low concentration of ropivacaine is extremely safe and effective for labor delivery analgesia [26,27] . Compared with continuous infusion, intermittent bolus administration of mixed drug of ropivacaine 0.1% with fentanyl 0.0002% provides a more efficacious route of drug delivery without adversely affecting maternal safety or satisfaction [28] . Our clinical trial demonstrated that the NA proposed by NPLD project was effective.…”
Section: Discussionmentioning
confidence: 99%
“…A neuraxial approach is accepted as the gold standard for intrapartum labor analgesia [26,27] . The mixed drugs of ropivacaine and fentanyl administrated by PCEA pump is extremely safe and effective for labor delivery analgesia [26][27][28] . Our clinical trial demonstrated that the NA proposed by NPLD was effective, which reduced the delivery pain from average 9.2 to 3.1 according to VAS and NRS.…”
Section: Discussionmentioning
confidence: 99%